In open field: Walter Benjamin and nature (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Although the interest of the philosopher Walter Benjamin for the urban space has been motivating exhaustive studies and analysis for a long time, the same cannot be said of his many reflections on the natural space. Trying to fill this gap, the article takes as its core a corpus of writings by the author that account for this interest –essay fragments, short stories, diaries, correspondence– in order to evaluate the philosophical variables that become evident in the contact of the German thinker with the landscape and the way the natural settings receive and determine his mood and his personal trajectory
Keywords: Walter Benjamin; nature; landscape; walking